(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2023)
This article provides a comprehensive overview of the contemporary approaches and advancements in the treatment of cardiovascular diseases within the field of cardiology. Through an analysis of current literature, we explore various methods ranging from traditional pharmacological interventions to cutting-edge interventional procedures. The review emphasizes the importance of a multidisciplinary approach, incorporating medications, lifestyle modifications, and innovative technologies to enhance patient outcomes.